Permeability measurement theory in case of natural gas and natural gas-hydrogen mixture - Bölkény, Ildi; Vadászi, Marianna; Saliby, Ammar (Analecta Technica Szegedinensia, 2023)
Green hydrogen, using renewable electricity that breaks down water molecules into hydrogen and oxygen, holds great promise for meeting global energy demand while contributing to climate policy goals. Interest in green hydrogen production technologies has increased considerably. This is because the potential uses of hydrogen cover many sectors, including power generation, manufacturing processes in steel and cement production, fuel cells for electric vehicles, and power grid stabilization. One possible use of green hydrogen is to blend it with natural gas and deliver it to end-users using existing natural gas pipeline storage and networks, thereby increasing performance and reducing emissions. In the case of underground storage of a hydrogen natural gas mixture, it is important to assess its impact on the reservoir beforehand, which rock permeability studies can do. This article deals with the theory of rock permeability testing for natural gas and natural gas-hydrogen mixtures.